Will the digital economy help reduce pressure on the environment? - Wysokińska, Zofia (W poszukiwaniu zielonego ładu, 2022)
The aim of the chapter is to present the digital transformation as a process taking place in the global economy and in the European Union in recent years and its impact on changes in the economic and social spheres, as well as building positive relations between digitization and environmental protection, towards a circular economy. The role of information and communication technologies, which are a key basis for the development of the digital economy, was also presented. The main topics discussed in this chapter are the role of the Digital Innovation Hubs and their positive impact on the integration of universities, research institutes and the business sphere to create new ideas and to shape new instruments to implement the concept of sustainable development, including the development of new skills and digital competences within the digital single market in the European Union, in particular the economy based on Big Data and open access to research results.